Blockade of CD73 Increases the Cytotoxic Effects of Fludarabine in Chronic Lymphocytic Leukemia - Mohammad Sadeghi; Mahsa Yousefi Bostanabad; Omid Abedi; Abbas Ali Hosseinpour Feizi; Ali Akbar Movasaghpour Akbari; Farhad Jadidi-Niaragh (ImmunoAnalysis, 2022)
Background: Ecto-5’-nucleotidase (CD73) is a membrane-bound enzyme that converts adenosine 5’-monophosphate into adenosine. It is proven that the presence of elevated levels of adenosine in the tumor microenvironment induces tumor growth while suppressing immune responses against tumor cells. According to several studies, it is reported that the expression of CD73 is increased in several types of malignancies. In chronic lymphocytic leukemia (CLL), a hematological malignancy characterized by the increased proliferation and accumulation of lymphoid cells in peripheral blood (PB) and lymphoid tissues, CD73 expression is associated with higher-risk disease. Moreover, it is reported that CD73 may contribute to fludarabine (a chemotherapeutic widely used for the treatment of CLL) resistance as well. Methods: We separated mononuclear cells obtained from PB and bone marrow (BM) from eleven CLL patients. Cells were treated individually or in combination with fludarabine and anti-CD73 siRNA (transfection by lipofectamine), and the effect of treatment on cell survival was evaluated using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) test. Results: We found that the highest level of apoptosis induction was observed in cells treated with fludarabine combined with CD73 inhibition, compared to the untreated (P<0.01). Our findings are in support of a study reporting the association between CD73 overactivation and fludarabine resistance. Conclusion: These findings suggest that CD73 inhibition can be a potential target for CLL treatment and can help overcome endurance towards fludarabine and can better the prognosis of CLL-affected individuals.